Search for W' → tb→ qqbb decays in pp collisions at √s = 8 TeV with the ATLAS detector - Alconada Verzini, María Josefina (2015)
A search for a massive W' gauge boson decaying to a top quark and a bottom quark is performed with the ATLAS detector in pp collisions at the LHC. The dataset was taken at a centre-of-mass energy of √s = 8 TeV and corresponds to 20.3 fb−1 of integrated luminosity. This analysis is done in the hadronic decay mode of the top quark, where novel jet substructure techniques are used to identify jets from high-momentum top quarks. This allows for a search for high-mass W' bosons in the range 1.5–3.0 TeV. b-tagging is used to identify jets originating from b-quarks. The data are consistent with Standard Model background-only expectations, and upper limits at 95% confidence level are set on the W' → tb cross section times branching ratio ranging from 0.16 pb to 0.33 pb for left-handed W' bosons, and ranging from 0.10 pb to 0.21 pb for W' bosons with purely righthanded couplings. Upper limits at 95% confidence level are set on the W'-boson coupling to tb as a function of the W' mass using an effective field theory approach, which is independent of details of particular models predicting a W' boson.